PENGARUH PEMBERIAN RANSUM BERSERAT KASAR BEDA TERHADAP BOBOT HIDUP DAN KARKAS AYAM JANTAN TIPE MEDIUM UMUR 8 MINGGU - Riki Dwi Haryadi; Rudy Sutrisna; Tintin Kurtini (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Ration nutrient content provided should be considered crude fiber content. Crude fiber can stimulate the digestive tract peristalsis so digestion of nutrients going smooth. This study aims to: (1) determine the effect of different diets on the coarse fibrous body weight, percentage of body weight, carcass weight and percentage rooster type of medium and (2) obtain the level of crude fiber in the diet best for body weight, percentage of body weight , weight and carcass percentage rooster medium type. This study was conducted in 12 September until 20 October 2014 located in the cage of Rama Jaya Farm, Karang Anyar, District Court Teak, South Lampung regency. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Ration percentage of crude fiber are R0: 4%, R1: 6%, R2: 8%, and R3: 10%. The resulting data were analyzed using ANOVA , if the variance analysis showed that the treatment of crude fibrous ration significantly different at 5% level , then the analysis followed by Least Significant Difference test ( LSD). Based on these results it can be concluded that: Giving a crude fibrous ration 4, 6, 8, and 10% not significant (P˃0,05) on body weight, percentage of body weight, carcass weight and percentage rooster type of medium age of 8 weeks.